INFLUENCE OF FAMILY CHARACTERISTICS AND CULTURAL NORMS ON PRE-MARITAL SEX AMONG SECONDARY SCHOOL STUDENTS IN OJO LOCAL GOVERNMENT AREA OF LAGOS STATE, NIGERIA - Oladipupo-Okorie, B.O.; Viatonu, Olumuyiwa (European Scientific Journal, ESJ, 2014)
The purpose of this study is to investigate the influence of family characteristics and cultural norms on pre-marital sex among secondary school students in Ojo Local Government Area of Lagos State, Nigeria. A simple random sampling technique was used to select 500 secondary school students in the Local Government Area. The instrument used for data collection was a 4-point Likert scale questionnaire designed by the researchers and validated by test and measurement experts in the Faculty of Education, Lagos State University Lagos, Nigeria. A test – retest of 0.76 was got when the instrument was subjected to Pearson’s Product Moment Correlation Coefficient (PPMC), which was an indication that the instrument was reliable and suitable for the study. The data collected were analysed using frequency count and simple percentages while inferential statistic of chi-square was used to test the hypotheses at 0.05 level of significance. The findings revealed that family characteristics and cultural norms were some of the factors responsible for pre-marital sex among secondary school students in Ojo Local Government Area of Lagos State. It was recommended that parents should model good sexual behaviour to their children, parents should also teach their children sexuality education and that children should do away with any cultural norms that could attract them to engage in pre-marital sexual act.